Effect of model heat treatment conditions on selected properties of milk fat. (21st February 2020) - Staniewski, Bogusław; Smoczyński, Michał; Żulewska, Justyna; Wiśniewska, Krystyna; Baranowska, Maria
Abstract : In this study, the effect of diverse thermal treatments on the physical characteristics of anhydrous milk fat was monitored with the use of scanning calorimetry, firmness analysis, electron microscopy and image analysis. The optimal properties of milk fat were achieved for the thermal treatment taking into account its composition as well as melting and solidification points of the main triacylglycerol fractions (temperatures: 6/20.5/14 °C). Unfavourable results were obtained for the one‐stage system (10 °C/13 h). These results may be helpful in optimising parameters of milk fat crystallisation in high‐fat products, and the fractal analysis has proven to be useful in the evaluation of fat crystallisation.